Diagnostic Accuracy of Assays Using Point-of-Care Testing or Dried Blood Spot Samples for the Determination of Hepatitis C Virus RNA: A Systematic Review . (12th February 2022) - Catlett, Beth; Hajarizadeh, Behzad; Cunningham, Evan; Wolfson-Stofko, Brett; Wheeler, Alice; Khandaker-Hussain, Benazir; Feld, Jordan J; Martró, Elisa; Chevaliez, Stéphane; Pawlotsky, Jean Michel; Bharat, Chrianna; Cunningham, Philip H; et al.
Abstract: Background: Finger-stick point-of-care and dried blood spot (DBS) hepatitis C virus (HCV) RNA testing increases testing uptake and linkage to care. This systematic review evaluated the diagnostic accuracy of point-of-care testing and DBS to detect HCV RNA. Methods: Bibliographic databases and conference presentations were searched for eligible studies. Meta-analysis was used to pool estimates. Results: Of 359 articles identified, 43 studies were eligible and included. When comparing the Xpert HCV Viral Load Fingerstick assay to venous blood samples (7 studies with 987 samples), the sensitivity and specificity for HCV RNA detection was 99% (95% confidence interval [CI], 97%–99%) and 99% (95% CI, 94%–100%) and for HCV RNA quantification was 100% (95% CI, 93%–100%) and 100% (95% CI, 94%–100%). The proportion of invalid results following Xpert HCV Viral Load Fingerstick testing was 6% (95% CI, 3%–11%). When comparing DBS to venous blood samples (28 studies with 3988 samples) the sensitivity and specificity for HCV RNA detection was 97% (95% CI, 95%–98%) and 100% (95% CI, 98%–100%) and for HCV RNA quantification was 98% (95% CI, 96%–99%) and 100% (95% CI, 95%–100%). Conclusions: Excellent diagnostic accuracy was observed across assays for detection of HCV RNA from finger-stick and DBS samples. The proportion of invalid results following Xpert HCV Viral Load Fingerstick testing highlights the importance of operator training and quality assurance programs. Abstract : HCV active infection can be accurately detected by assays that utilize point-of-care testing or dried blood spot samples for the determination of HCV RNA.